Best industry outcomes - Crawford, Lynn; Cooke-Davies, Terry, 1941- (Project Management Institute, 2012)
Of Key ResultsSummary of Results by Industry Sector; Aerospace and Defense; Automotive; Engineering and Construction; Fast Moving Consumer Goods (FMCG); Financial and Business Services; Government; IT and Telecommunications; Pharmaceutical; Utilities; Concluding Remarks, Limitations, and Future Research; References; Appendices; Appendix A: Phase One Interview Protocols; Appendix B: Research Ethicsâ#x80;#x94;Consent Forms; Appendix C: Abbreviated Questions for Tables and Charts; Appendix D: Bivariate Analysis; Appendix E: Categorization and Regression Trees for Each OPM Outcome.
Title from title screen.
Keywords: Project management -- Research.; elektronické knihy; electronic books